Maize yields in a Mucuna pruriens var. Utilis and Pueraria phaseoloides relay fallow system on an Ultisol in southern Cameroon - Hauser, S.; Hauser, A.; Henrot, J. (Informa UK Limited, 2002)
Nitrogen nutrition of sole maize crops is problematic in ‘no-input’ agricultural systems. The ability of the N2 fixing cover crops. Mucuna pruriens var. utilis and Pueraria phaseoloides, to sustain annual cropping of sole maize was tested from 1997 to 2000, with the fallow biomass either burned or retained. In 1997, 1999 and 2000, maize grain dry matter yield was significantly higher after M. pruriens and P. phaseoloides than after natural fallow regrowth. The fallow type had no effect on grain yield in 1998. Burning of the biomass before planting maize increased grain yield in 1998 but had no effect in 1997, 1999 and 2000. The cumulative grain yield over 4 years was 9.14 Mg ha in the natural fallow regrowth, significantly less than after M. pruriens (11.73 Mg ha) and P.phaseoloides (12.54 Mg ha). Burning the biomass, although nonsignificant in 3 out of 4 years, had a cumulative advantage with 11.72 Mg ha grain yield, compared with biomass retention (10.55 Mg ha, p = 0.0 19). The economically important yield of marketable cobs was on average approximately US$320 ha year higher after burned P. phaseoloides cover crop than after burned natural fallow regrowth. The lack of a positive yield response to biomass and thus N retention was related to problems of maize establishment. The nitrogen contained in the aboveground cover crop biomass appears not to the essential for maize nutrition under the site conditions.